Prototyping of an alternative communication resource for the person with laryngeal cancer tracheostomy (Research, Society and Development, 2021)
Objective: to carry out the prototyping of an alternative communication mobile application for people with laryngeal cancer tracheostomy, based on the Wanda Horta's theory of Basic Human Needs. Methods: application study of the Pressman prototype creation model, with the adoption of the paper format due to the adequacy of the presentation of the technological conception, with the implementation of the definition and development phases. As this is a research in the Nursing area, Wanda Horta's Theory of Basic Human Needs was adopted, focusing on communication. Results: the proposed prototype was the intervention in view of the interruption of the communication process of these patients. Final considerations: the prototyping method enabled the conception of a technology, with the planning and detailed discussion of each of the stages, confirming the feasibility of developing a software, in this case a mobile application, based on the Theory of Basic Human Needs linked to the Nursing Process.